Effect of thermal annealing on low-energy C-ion irradiated MgB2 thin films - Jung, S.-G.; Son, S.-K.; Pham, D.; Lim, W.C.; Song, J.; Kang, W.N.; Park, T. (Korea Institute of Applied Superconductivity and Cryogenics, 2019)
We investigate the effect of thermal annealing on MgB2 thin films with thicknesses of 400 and 800 nm, irradiated by 350 keV C-ions with a dose of 1 x 1015 atoms/cm2. Irradiation by low-energy C-ions produces atomic lattice displacement in MgB2 thin films, improving magnetic field performance of critical current density (Jc) while reducing the superconducting transition temperature (Tc). Interestingly, the lattice displacement and the Tc are gradually restored to the original values with increasing thermal annealing temperature. In addition, the magnetic field dependence of Jc also returns to that of the pristine state together with the restoration of Tc. Because Jc(H) is sensitive to the type and density of the disorder, i.e. vortex pinning, the recovery of Jc(H) in irradiated MgB2 thin films by thermal annealing indicates that low-energy C-ion irradiation on MgB2 thin films primarily causes lattice displacement. These results provide new insights into the application of low-energy irradiation in strategically engineering critical properties of superconductors. ？ 2019, Korea Institute of Applied Superconductivity and Cryogenics. All rights reserved.
Keywords: Annealing; Critical current density (superconductivity); Heavy ions; Ion bombardment; Magnesium compounds; Magnetic fields; Restoration; Superconducting films; Superconducting transition temperature; Thin films; Atomic lattice; Critical properties; Lattice displacement; Low energy irradiation; Magnetic field dependences; MgB2 thin films; Thermal-annealing; Vortex pinning; Boron compounds